A relação entre as características dos CEOs e a agressividade fiscal das empresas - Rodrigues, Jessica de Paula (2019)
This research aims to study the relationship betwenn the professional charecteristics of the CEOs and company’s tax aggressiveness. The impact of brazilian taxation on the companies is widely discussed in the accounting literature. The dissatisfaction with the government return, along with the high tax expense inherent to the companies create a growing search to reduce the amount paid in taxes. Tax aggressiveness can be also defined as risky tax planning which uses loopholes in legislation to pay less taxes. To identify the level of tax aggressiveness fo the companies, three metrics were used: Cash Effective Tax Rate – Cash ETR, Book-tax Differences e Effective Tax Rate, widely used in the tax aggressiveness literature internationally. The study used binomial logistic reggression in order to identify the impacto f the CEOs professional charecteristics in company’s tax aggressiveness. The research sample consists of the companies in the brazilian stock, B3, and the information are from the years of 2010 to 2017. The results show that there is positive relation between the CEOs and tax aggressiveness, specially when experienced in administration board, graduated in accounting, economy and engeneering. The study implies that the subject must be put to further detailed research.